Study on the Evaluation Method of Marine Comprehensive Carrying Capacity: Taking Yancheng Sea Area of China as an Example. Issue 5 (April 2020) - Jin, Ru; Li, Fei; Gao, Yijian
Abstract: With the rapid growth of China's economy since the start of the 21st century, the development and utilization of coastal areas have also experienced rapid expansion. With the continuous and high-intensity agglomeration of social and economic factors such as city, industry and population in coastal areas, the fragile and sensitive coastal ecosystem is under great pressure of resources and environment. In this study, we propose a theoretical and methodological framework for the comprehensive evaluation of the sea area carrying capacity to systematically evaluate the coupling and coordination of resources, environment and development in coastal areas. This framework includes 12 representative indicators of three factors: spatial resource endowment, ecological environment pressure and development and utilization intensity. Taking Yancheng sea area of China as an example, we analyzed the development and change of sea area carrying capacity from 2000 to 2015. The results show that the carrying capacity score of Yancheng sea area decreased from 3.12 in 2000 to 1.58 in 2015, indicating that the comprehensive carrying capacity of the sea area in this period is facing an unsustainable severe situation. At the same time, with the development intensity index score increasing from 0.62 to 0.92, the resource endowment index and ecological environment index scores decreased from 0.98 to 0.75 and 0.95 to 0.70, respectively, indicating that the continuous high-intensity development activities in Yancheng sea area during this period put great pressure on resources and environment. This framework can provide technical support for the balance of economic development and the protection of resources and environment in coastal areas.